Prevalence and factors associated with preoperative anemia among adult patients scheduled for major elective surgery at University hospital in Northwest Ethiopia; a cross-sectional study. Issue 2 (February 2022) - Beyable, Amare Anley; Berhe, Yophtahe Woldegerima; Nigatu, Yonas Addisu; Tawuye, Hailu Yimer
Abstract: Background: Anemia is the most common hematological finding in surgical patients. One-third of surgical patients were anemic during preoperative assessment. The presence of preoperative anemia was found to be related with increased morbidity, mortality, length of hospital stay, intensive care unit admissions and postoperative infections. Objective: To determine the prevalence and factors associated with preoperative anemia among adult patients scheduled for major elective surgery at University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2020. Methods: After obtaining an ethical approval, hospital-based cross-sectional quantitative study was conducted from June to August 2020 in University of Gondar Hospital. Full blood count within two weeks of preoperative period was considered valid if there were no any factors that affect the hematologic system Descriptive statistics, cross-tabulations and binary logistic regression analysis were performed to identify factors associated withpreoperative anemia. The strength of the association was presented using AOR with 95% confidence interval and p-value < 0.05 was considered as statistically significant. Result: A total of 185 patients enrolled with 100% response rate. We observed preoperative anemia in 36.8% patients. The multi-variable binary logistic analysis showed that ASA II and III [AOR: 3.8, CI: 1.6–9.2], recent prior surgery [AOR: 3.3, CI: 1.3–8.5], history of malignancy [AOR: 9.4, CI: 2.0–43.4], orthopedic procedure [AOR: 11.2, CI: 4.0–31.6] and gynecologic procedure [AOR: 5.2, CI: 1.7–14.5] were significantly associated with preoperative anemia. Conclusion: The prevalence of preoperative anemia was high and ASA ≥2, recent prior surgery, history of malignancy, orthopedic surgery and gynecologic procedure were significantly associated with preoperative anemia. We recommend to clinicians to aim prevention, early detection and treatment of preoperative anemia among adult patients scheduled for major elective surgery to reduce risk of anemia and related adverse outcomes. Abstract : Anemia; Preoperative anemia; Anemia and elective surgery; Preoperative care.